KNOWLEDGE AND SELF-AWARENESS AS DETERMINANTS OF OCCUPATIONAL SAFETY AND HEALTH PRACTICES AMONG NURSING STUDENTS - Wardhani, Utari; Sri Muharni; Rahmadillah Muhti (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Safety and health education in the laboratory is critical because laboratories are high-risk environments that can increase the incidence of workplace accidents. Problems arise when students' knowledge and self-awareness are lacking, including exposure to sharp objects such as syringes, bodily fluids, and pathogens, as well as ignorance of reporting work accidents and the risk of injury. The purpose of this study is to analyze the relationship between the level of knowledge and self-awareness of nursing students and OSHA practices in the nursing laboratory of Awal Bros University. This study uses a quantitative approach with a cross-sectional design. The sample in this study consisted of 167 nursing students selected through a total sampling technique. Data were collected using a questionnaire that included variables of knowledge, self-awareness, and OSHA practices, and then analyzed using Chi-Square tests. The research results show that 64.1% of respondents have good OHS knowledge, 48.5% have high self-awareness, and 64.7% practice OHS well. The statistical test results found that there was a significant relationship between knowledge and occupational safety and health practices (p-value = 0.000) as well as self-awareness and OSH practices (p-value = 0.000). In conclusion, there is a significant positive relationship between nursing students' knowledge and self-awareness with OHS practices in the laboratory. Therefore, it is recommended that future researchers reach out to other, more diverse institutions and consider other variables, such as practical experience, that may influence students' knowledge and self-awareness. In addition, qualitative or mixed research methods can be used to explore student behavior in implementing OHS.